2016
DOI: 10.1589/jpts.28.1816
|View full text |Cite
|
Sign up to set email alerts
|

The effects of eye movement training on gait function in patients with stroke

Abstract: [Purpose] The present study examined the effects of eye movement training on gait function in patients with stroke. [Subjects and Methods] Fourteen patients with stroke were randomly assigned to either an experimental group or a control group. The experimental group underwent eye movement training while the control group underwent general gait training five times per week for six weeks. [Results] Patient walking speed, cadence, and step length were measured by ink-footprint. The experimental group exhibited si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Beyond that, saccadic eye movement training as a gait rehabilitation strategy could be an important therapeutic option. Some studies have reported saccadic eye movement training as a strategy for alleviating gait abnormalities in terms of improvement in stance time and accuracy in stepping in patients ( Table 3 ) [ 193 - 195 ].…”
Section: Saccades and Gait In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Beyond that, saccadic eye movement training as a gait rehabilitation strategy could be an important therapeutic option. Some studies have reported saccadic eye movement training as a strategy for alleviating gait abnormalities in terms of improvement in stance time and accuracy in stepping in patients ( Table 3 ) [ 193 - 195 ].…”
Section: Saccades and Gait In Neurodegenerative Diseasesmentioning
confidence: 99%
“…According to a previous study, VRT may improve the vestibulo-ocular reflex function and gait control in patients with vestibular disease and stroke hemiparesis [36]. It has been reported that eye movement training in post-stroke survivors brought about significant changes in walking speed, cadence, and step length over time, resulting in significant differences following training [37].…”
Section: Discussionmentioning
confidence: 97%
“…Another study reported that vestibular rehabilitation treatment including gaze stabilization exercises had a positive effect on the gait ability of acute stroke patients [ 57 ]. There is also a study that reported that an eye exercise program using cards and tools improved retaliation, gait speed, and cadence in stroke patients [ 58 ]. This study showed that gait can be improved if the visual and vestibular organs are directly stimulated.…”
Section: Discussionmentioning
confidence: 99%